2017
DOI: 10.1536/ihj.16-208
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cardiovascular Risks of Proton Pump Inhibitors in the General Population

Abstract: SummaryProton pump inhibitors (PPIs) are the most effective gastric acid-suppressing agents and the mainstay medical therapy for a series of acid peptic diseases. In general, the safety profile of PPIs is excellent. However, with long-term drug administration, the safety and potency of PPIs has been questioned. In the cardiovascular field, drug-drug interactions related to PPIs have been identified with particular attention regarding the use of PPIs combined with clopidogrel in patients with acute coronary syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
(40 reference statements)
0
8
2
Order By: Relevance
“…Nevertheless, like in the case of other drugs, PPIs are not as safe as it has been thought and more recently, concerns have been raised about their potential association with pneumonia[ 65 - 67 ], bone fractures[ 68 - 70 ], interstitial nephritis and acute kidney injury[ 71 ]. More recently, reports of other potential PPIs adverse events such as risk for chronic kidney disease[ 72 , 73 ], dementia[ 74 ], spontaneous bacterial peritonitis[ 75 , 76 ], acute myocardial infarction[ 77 , 78 ], micronutrient deficiency (magnesium, calcium, iron)[ 79 , 80 ] were published, although the quality of evidence for these is consistently low to very low[ 81 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, like in the case of other drugs, PPIs are not as safe as it has been thought and more recently, concerns have been raised about their potential association with pneumonia[ 65 - 67 ], bone fractures[ 68 - 70 ], interstitial nephritis and acute kidney injury[ 71 ]. More recently, reports of other potential PPIs adverse events such as risk for chronic kidney disease[ 72 , 73 ], dementia[ 74 ], spontaneous bacterial peritonitis[ 75 , 76 ], acute myocardial infarction[ 77 , 78 ], micronutrient deficiency (magnesium, calcium, iron)[ 79 , 80 ] were published, although the quality of evidence for these is consistently low to very low[ 81 ].…”
Section: Introductionmentioning
confidence: 99%
“…16) Furthermore, these risks may extend from patients with coronary artery disease to the general population. [17][18][19][20][21] However, there are several studies with conflicting results that PPIs do not manifest as an independently increased risk of adverse cardiovascular events. 22,23) To help address this association, a metaanalysis of randomized controlled trials (RCTs) demonstrated that PPI monotherapy could be a risk factor for adverse cardiovascular events in patients with gastroesophageal reflux disease (GERD).…”
mentioning
confidence: 99%
“…Furthermore, we could not rule out the possibility that the cardiovascular risk may be additionally increased by mechanisms other than the attenuated effectiveness of clopidogrel due to CYP2C19 inhibition by concomitant PPI. A recent study suggested that PPIs may increase cardiovascular risk by inhibiting dimethylarginine dimethylaminohydrolase activity, leading to increased superoxide anion generation, reduced nitric oxide generation, and impaired vascular homeostasis . In contrast, previous studies showed no association between PPI use and adverse events among patients not receiving clopidogrel, indicating the need for further studies …”
Section: Discussionmentioning
confidence: 95%